Systematics studies in Pliniinae (Myrtaceae) necessitate two new combinations in Eugenia (Myrtaceae) - Stadnik, Aline; Caldas, Diana K. D.; Souza, Marcelo C.; Lucas, Eve J.; Baumgratz, José Fernando A.; Roque, Nádia (Phytotaxa, 2021)
Although Eugenia and Plinia genera belong to different subtribes in Myrteae (Myrtaceae), shared morphological features have led to frequent mistaken identity to these species. Molecular phylogeny and morphological studies in Plinia show that Plinia martinellii and Plinia sebastianopolitana should be combined within the generic concept of Eugenia. In addition, two synonymizations under Plinia sebastianopolitana and one under Plinia martinellii are proposed. Commentary on these nnomenclatural adjustments, as well as on morphological and geographical data related to the evolution of these lineages is also provided.